Combination of ROC and MFEP Methods on the Acceptance of Rainwater Gutter Installer - Victor Tarigan; Lintang Patria; Aditiarno Manik; Pujo Hari Saputro (SAGA: Journal of Technology and Information System, 2023)
The services of building construction companies in today's modern era are increasingly in demand by the wider community to get the best building results. Installing a rainwater tap in a building is one of the most important parts to pay attention to so that consumers are not disappointed. Therefore, the head of a building construction company that offers services in this field must be careful in the process of accepting rainwater gutter installer. The criteria used to acceptance of rainwater gutter installerin this study consisted of insight, work experience, health, and age criteria. Data collection techniques used in this study were literature studies and field studies. In this study the authors apply the ROC and MFEP methods to obtain the decision making of acceptance of rainwater gutter installer. In the results of this study an alternative named Rudiasyah (0.427111) has the highest value compared to other alternatives. So in this study Rudiasyah became the most recommended alternative to be accepted as a rainwater gutter installer